Synthetic Indicator's Evaluation of the tuberculosis program. Health Areas I and II. Cienfuegos 2013 - Narciso Águila Rodríguez; Tamara Montenegro Calderón; Hilda María Delgado Acosta; María Lina Valdés Gómez; Lizette Rodríguez Fernández; Eneida Bravo Polanco (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: Along the years, in the National Program of Prevention and Control of Tuberculosis of Cuba several changes have been done as those related to its evaluation, including new synthetic indicators. Objective: to evlautae the synthetic indicators for the location and detection of new cases of pulmonary tuberculosis. Methods: descriptive research in health services and systems realized in health areas I and II of the Cienfuegos Municipality in the years 2013. The information was taken from the Department of Statistics of the Health Areas. The processing of the data to calculate the indicators was done with the program CALIND designed in Access, used with purpose in the Institute Pedro Kouri. Percentage and incidence rate were used as a Mathematical measures for the quantitative data analysis. Results: the application of the synthetic indicator was used to assess the quality of location of the tuberculosis cases in Area I. It was evaluated as deficient in this area and acceptable in Area II. The synthetic indicator was evaluated as deplorable in Area I and poor in Area II. Conclusion: the application of synthetic indicators for locating and detecting cases of Tuberculosis is coherent with the reality about the quality of case detection. It is corroborated its effectiveness to assess the process in the Program of Prevention and Control of Tuberculosis.